2015
DOI: 10.1172/jci84690
|View full text |Cite
|
Sign up to set email alerts
|

Over-salting ruins the balance of the immune menu

Abstract: C o m m e n t a r y 4 0 0 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…As previously demonstrated, increased plasma Na + has high pro-inflammatory potential through both enhancing proinflammatory responses and impairing regulatory mechanisms13738. It turned out that the vascular endothelium is sensitive to a small rise in Na + concentrations, such that a defined range of extracellular Na + concentrations tightly links the mechanical properties to NO production6.…”
Section: Discussionmentioning
confidence: 95%
“…As previously demonstrated, increased plasma Na + has high pro-inflammatory potential through both enhancing proinflammatory responses and impairing regulatory mechanisms13738. It turned out that the vascular endothelium is sensitive to a small rise in Na + concentrations, such that a defined range of extracellular Na + concentrations tightly links the mechanical properties to NO production6.…”
Section: Discussionmentioning
confidence: 95%
“…However, NaCl itself is proinflammatory and has been shown to induce T H 17 cells while conversely inhibiting forkhead box protein 3 + regulatory T-cell function 38 , 39 and to also activate inflammatory cascades in monocytes and bone marrow–derived macrophages in vitro . 40 , 41 The saline control that we used in the current study contained 0.9% NaCl, which is similar to the concentration used in the diluent of the VZV skin test antigen (0.68% NaCl). Therefore a component of the transcriptional response of old subjects to VZV antigen would also include a response to NaCl in the diluent that might hinder the induction of antigen-specific immunity in old subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an HSD can induce human circulating monocyte proinflammatory activation and is associated with monocyte-platelet aggregation [13]. Moreover, the activation and function of dendritic cells, M1 macrophages are stimulated on an HSD, while M2 macrophages are blunted found in vitro and in vivo [14][15][16], accompanied by increased activation of pro-IL-1β, nuclear factor-κB, and p38/mitogen-activated protein kinase (MAPK)-dependent nuclear factor of the activated T-cell 5 (NFAT5) signaling, and elevated NO production [14,17,18]. Interestingly, studies found that macrophages in turn might be pivotal regulators of salt homeostasis by a TonEBP-VEGF-C-dependent buffering mechanism, since the NaCl hypertonicity was proved to stimulate macrophages to migrate in the direction of excess salt concentration in vitro [19].…”
Section: Hsd Influence the Immune Systemmentioning
confidence: 99%
“…These proteins are important in the pyrimidine metabolism, ATP binding, materials transferring, cell cycle, and cell division. On the other hand, the HSD was found to exert a synergistic effect with Helicobacter pylori on the development of gastritis [7,8] and H. pylori-associated carcinogenesis [15,20,23,48]. Studies demonstrated that HSD can alter H. pylori gene expression while modulating H. pylori-induced virulence factors such as cytotoxinassociated gene A (CagA) [45] and vacuolating cytotoxin (VacA) [21,23,49].…”
Section: Hsd Alters the Gut Microbiota Functionmentioning
confidence: 99%